2016
DOI: 10.1002/cncr.30337
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing and targeted gene sequencing provide insights into the role of PALB2 as a male breast cancer susceptibility gene

Abstract: These results add strength to the evidence showing that PALB2 is involved in BC risk for both sexes and indicate that consideration should be given to clinical testing of PALB2 for BRCA1/2 mutation-negative families with multiple MBC and FBC cases. Cancer 2017;123:210-218. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
5
17
0
Order By: Relevance
“…Among non‐ BRCA1/2 genes a significant role of PALB2 in MBC susceptibility emerged. We have previously shown that PALB2 plays a relevant role in high‐risk, non‐ BRCA1/2 MBC cases . In the present study, more than 1% of non‐ BRCA1 / 2 MBC cases, unselected for FH of BC/OC had a germline PALB2 pathogenic variant.…”
Section: Discussionsupporting
confidence: 44%
“…Among non‐ BRCA1/2 genes a significant role of PALB2 in MBC susceptibility emerged. We have previously shown that PALB2 plays a relevant role in high‐risk, non‐ BRCA1/2 MBC cases . In the present study, more than 1% of non‐ BRCA1 / 2 MBC cases, unselected for FH of BC/OC had a germline PALB2 pathogenic variant.…”
Section: Discussionsupporting
confidence: 44%
“…Two high-penetrance breast cancer genes, BRCA1 and BRCA2, are thought to be responsible for only 13% of MBC (71), and multiple genetic factors remain unknown. To date, many PVs of PALB2 have been reported in MBC patients (72)(73)(74)(75)(76). In 2017, Pritzlaff et al uncovered that PALB2 variants significantly increased the risk of MBC (OR, 6.6; p = 0.01) (77).…”
Section: Palb2 and Breast Cancermentioning
confidence: 99%
“…Indeed, different studies have been carried out through the European continent to determine the role and the implication of BRCA1 and BRCA2 genes in BC, as well as detect novel mutations [ 50 – 72 ]. Other genes have been studied in both African and European continents and revealed to be associated with BC, such as CHEK2 [ 52 , 65 , 73 75 ], TP53 [ 73 , 76 , 77 ], MTHFR [ 78 ], PALB2 [ 79 81 ]. Whereas, other genes have been proved involved in BC development solely in Africa such as APOBEC3A, APOBEC3B, ARID1B, NCOR1, SMAD4, MAP3K1, HER2, HER and RAD50 or only in Europe such as RAD51 [ 82 84 ], COMT [ 85 , 86 ], CYP17 [ 86 ], MRE11A [ 61 , 87 ], CYP19 [ 87 ] and MDM2 [ 88 ].…”
Section: Discussionmentioning
confidence: 99%